Effectiveness of Several Bioactivators on the C/N Ratio and Potassium (K) and Manganese (Mn) Nutrition Content of Coffee Skin Compost (Coffea sp) - Sri Pratiwi Aritonang; Efbertias Sitorus; Sri Rahayu; Hariyati Lubis; Ilfa Husna Pulungan (Talenta Publisher, 2026)
Coffee skin waste is an abundant agricultural byproduct that can be converted into compost to support sustainable waste management. This study aimed to determine the effectiveness of several bioactivators, namely EM-4, BioTRIBA, and M-Dec, on the C/N ratio and potassium (K) and manganese (Mn) content of coffee skin compost. The research used a completely randomized design with eight treatments and three replications: EM-4 at 10 mL/L, BioTRIBA at 8, 10, and 12 mL/L, and M-Dec at 8, 10, 12, and 14 g/L. Composting was carried out for four weeks, and the observed parameters included pH, temperature, C/N ratio, C-organic, N-total, K-total, Mn-total, and moisture content. The results showed that all treatments reduced the C/N ratio from an initial value of 13.69% to a range of 10.65%–12.16%. The lowest C/N ratio was obtained in the M-Dec 10 g treatment (10.89%), indicating the most effective decomposition process. Potassium content decreased from 5.01% to 3.84%–4.30%, while manganese content increased significantly from 0.01 mg/kg to 108.16–132.25 mg/kg across treatments. The highest Mn accumulation was observed in the M-Dec 8 g treatment (132.25 mg/kg). Among all treatments, M-Dec 10 g was identified as the most effective treatment based on the lowest C/N ratio and balanced nutrient profile, meeting compost quality standards (SNI 19-7030-2004). Overall, the use of bioactivators accelerated decomposition and improved the quality of coffee skin compost, and M-Dec 10 g was the most effective treatment for meeting compost quality standards.